Preconception Risk Factors and Preconception Care Practices in a Hospital Based Turkish Sample - CAN GÜRKAN, ÖZLEM (MARMARA UNIV, INST HEALTH SCIENCES, 2021)
Objective: The aim of the study was to evaluate the preconception risk factors that may adversely affect pregnancy outcomes, and preconception care practices. Methods: A descriptive study was completed with 359 women. The data were collected with a questionnaire that was drawn up by the researchers. Results: Findings demonstrated that preconception risk factors were advanced age (20.6%), smoking (23.1%), existence of a chronic illness (23.6%) and being overweight (26.7%). Applied to a health institution to receive preconception care was 12.3 %. The most common preconception care practices were the use of folic acid (45.4%) and applying to the doctor for reorganization of the treatment for chronic illness (41.2%). Conclusion: The data showed that women had preconceptional risk factors and did not receive adequate preconceptional care. Women need to be provided with awareness on preconception risk factors. Policies should be developed to increase the frequency of women receiving preconception care.
Keywords: Preconception care; preconception risk factors; health behavior; pregnancy; PREGNANCY; OUTCOMES; HEALTH; WOMEN